ANALISIS PEMETAAN WILAYAH KABUPATEN DAN KOTA DI SUMATERA BARAT BERDASARKAN BELANJA MODAL, PERTUMBUHAN EKONOMI DAN KEMISKINAN - Hari Adria; Akhirmen Akhirmen; Melti Roza Adry (Universitas Negeri Padang, 2017)
The aims of this research to mapping of the region in West Sumatera Province based on capital expenditure with economic growth and capital expenditure with poverty, this research is descriptive analysis which is described in the form of quadrant table and klassen tripology analysis, where grouping based on capital expenditure with economic growth yields that from in 2011 to 2016 the district / city average in West Sumatra is in the worst quadrant of the fourth group, where capital expenditure is low and low economic growth is Pesisir Selatan District, Sijunjung Regency, Tanah Datar Regency, Padang Pariaman Regency, Agam Regency, Pasaman, South Solok District and Pariaman City. Furthermore, grouping based on capital expenditure with poverty resulted that from 2011 to 2016 the average of Regency / city in West Sumatera was in the first group I quadrant not yet ideal, where high capital expenditure has not been able to reduce poverty level such as Mentawai Islands Regency, Pesisir Selatan Regency, 50 Kota Regency, Pasaman Regency, Pasaman Barat Regency.